Rethinking Prison Sex: Self-Expression and Safety - Smith, Brenda V. (Columbia Journal of Gender and Law, 2006)
At the risk of buying into popular stereotypes about sex behind bars and the archetypes of the dyke prison matron providing better treatment to women in prison in exchange for sex, or torrid sex between women in prison, or the burly male prison rapist who creates prison wives, or the young man “turned out” in prison, I plan to explore the complexity of prison sex and the challenges that it raises in the context of recently enacted federal legislation, the Prison Rape Elimination Act (“PREA”). The primary focus of this Article is to begin to frame the discussion of prison sexuality and to chart an analytical framework for examining it. This Article is by no means exhaustive and seeks primarily to mark the terrain-leaving unexplored many areas that might prove fruitful for further research. This is the beginning of a project that will hopefully result in greater scholarship and analysis of prison sexuality from a multidisciplinary perspective.